Global trends in care seeking and access to diagnosis and treatment of childhood illnesses - Bennett, Adam; Eisele, Thom; Keating, Joseph; Yukich, Josh (DHS Working Papers No. 116, 2015)
Diarrhea, malaria, and acute respiratory infection (ARI) are among the leading causes of child mortality worldwide, with the greatest burden concentrated in developing countries. Child mortality has declined in recent years as a result of socioeconomic development and affordable and effective prevention and treatment options, yet many countries in Asia and Africa are not on track to meet Millennium Development Goal (MDG) 4—to reduce child mortality by two-thirds by 2015. Although evidence suggests that an increase in targeted interventions can accelerate child survival, a strong health care system is a necessary prerequisite for sustained reductions in preventable child deaths. An investigation into commonalities across countries and regions is needed to understand trends in treatment-seeking behavior and how sociodemographic and cultural factors interact to influence treatment-seeking modalities. This information will strengthen efficient delivery of care across all levels of the health system. Although many studies have documented barriers to accessing quality care, systematic analysis of these barriers is lacking. Yet large amounts of data are currently available (1) to identify and quantify the major barriers hindering access to quality care, and (2) to specify where these barriers are most prominent, relative to health care needs at the subnational level.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This study was carried out with support provided by the United States Agency for International Development (USAID) through The DHS Program (#GPO–C–00–08–00008–00). The views expressed are those of the authors and do not necessarily reflect the views of USAID or the United States Government. The DHS Program assists countries worldwide in the collection and use of data to monitor and evaluate population, health, and nutrition programs. For additional information about The DHS Program contact: DHS Program, ICF International, 530 Gaither Road, Suite 500, Rockville, MD 20850, USA; Phone: +1 301-407-6500; Fax: +1 301-407-6501; Email: reports@dhsprogram.com; Internet: www.dhsprogram.com.